Captura de dados do barramento CAN com uso da eletrônica embarcada em uma colhedora de grãos - Sampaio, Guilherme da Silva (2022)
Agricultural machinery has a bus for serial data communication, in which data from all the systems and sensors in the machinery flow. Thus, access to this data enables the control of additional implements that can be inserted for other purposes. Bean grain dirt is detrimental to the quality and value of the beans; therefore, farmers apply residues that reduce the dirtiness of the beans for a better product. However, the residue distribution equipment has no control over the distribution rate, causing problems of lack or excess product. The present study proposed a system for data collection from agricultural machines, which uses resources and implements embedded electronic devices to collect and decode specific CAN (Controller Area Network) bus data in grain harvesters. Devices and adapters were purchased to be connected to the machinery to collect data from the CAN bus. The data collection results in this study were inconclusive since the manufacturers of agricultural machines use locks in their machine systems, making it impossible for the owners to repair and access the machine systems. Another alleged cause of this adversity in CAN data collection is that some manufacturers do not follow the standard J1939 diagnostic port pinning, thus, making it impossible to correctly couple the CAN port, a situation that was experienced in tests of this study. The methodology selection proved to be satisfactory, delivering reliability to the project and consisting of a system implemented with embedded electronic devices (hardware), which are correctly interconnected, enabling a data collection system that can be used in future studies. The software used in the project proved to be accessible and attainable for implementation in the proposed system; the PolyCAN software proved capable of being implemented in CAN system projects due to its resources, being processed by the Raspberry Pi and accessed remotely via VNC Viewer. The present work contributes to and encourages future studies in the area of embedded systems in agricultural machines, which highlights the insufficiency of specific studies in the area, presents problems faced by farmers who want to repair their machinery, and the importance of investments in laboratories that cooperate for studies of embedded systems in agricultural machines